Computation of periodic magnetic field in ferromagnetic conductive medium and supply current harmonics by using harmonic balance finite element method - Petukhov, I.S. (Технічна електродинаміка, 2017)
The harmonic balance finite element method for two dimensional periodic magnetic field in a conductive ferromagnetic medium is formulated. To convert of partial differential equation system into the system of nonlinear algebraic equations the weak formulation of Galerkin method is used. Structural steel and silicon steel with different magnetic properties and various electrical conductivity are studied. It is described how to take into account the nonlinear properties of medium in mathematical model. The spectrum of supply current and flux density on the surface and inside the medium were computed provided the sinusoidal voltage fed. The dependencies of the amplitudes of high harmonics versus the steel properties and amplitude of the first harmonic of magnetic flux density at the surface of medium are presented. Представлено метод гармонічного балансу сумісно з методом скінченних елементів для двовимірного магнітного поля в електропровідному феромагнітному середовищі. Для перетворення диференціального рівняння в часткових похідних до системи нелінійних алгебраїчних рівнянь використовувався метод Гальоркіна в слабкому формулюванні. Досліджувалися конструкційна та легована сталь із різними магнітними властивостями та різною електропровідністю. Описано врахування нелінійних властивостей у математичній моделі. Розраховано спектри струму живлення та магнітної індукції на поверхні та всередині середовища за умов живлення синусоїдальною напругою. Представлено залежності амплітуд вищих гармонік від властивостей сталі та амплітуди першої гармоніки магнітної індукції на поверхні середовища. Сформулирован метод гармонического баланса совместно с методом конечных элементов для двумерного магнитного поля в электропроводящей ферромагнитной среде. Для преобразования дифференциального уравнения в частных производных в систему нелинейных алгебраических уравнений использовался метод Галеркина в слабой формулировке. Исследовались конструкционная и легированная сталь с различными магнитными свойствами и различной электропроводностью. Описан учет нелинейных свойств в математической модели. Рассчитаны спектры тока питания и магнитной индукции на поверхности и внутри среды при условиях питания синусоидальным напряжением. Представлены зависимости амплитуд высших гармоник от свойств стали и амплитуды первой гармоники магнитной индукции на поверхности среды.